(3OjhGf HgGA GdOjf RgjQs - (3HgGA GdOjf RgjQs ((3eMeO Hf jMji s)
(3ChdgG (B:s
(3GdMeO ddg GdPi NU HGdaVGFd ef TGA ef GdYHGO , GdbGOQ Ydi EYGOI ef eVi ceG XgQJ bOQJg ajef CHGA hChd GdTYQ Ydi bGajI GdCda bhdg (B: (3LRi Gddg Yfi GdMH NjQkG aEfg s
(3BNQgG (B:s
(3BNQg ef bUjOI dg ef eLRhA GdQed (B: (3jGdgG djdI hUd eKdgG dGjJgjC s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3eQJH Ydi MQha GdeYLe cJHJ GdYfhGfGJ HGdMeQIs
(3HBNQgG JQLeI dUGMH GdOjhGf efbhdI Yf JGQjN GHf NdcGf s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs